Pengaruh Temperatur Terhadap Entalpi dan Kinetic Rate Gas Pirolisis Kayu Mahoni - Suwandono, Purbo; Wijayanti, Widya; Hamidi, Nurkholis (Jurnal Rekayasa Mesin, 2015)
This study was conducted to determine the effect of temperature on gas enthalpy and kinetic rate of mahogany wood powder pyrolysis results. Research process carried out experimentally with the temperature 673 K, 773 K, 873K, 973 K and 1073 K. Pyrolysis process is carried out for 2 hours with a particle size of sawdust from 0.5 to 1 mm. The results showed that the enthalpy value increase as the temperature increase. Highest enthalpy value achieved at 1073 K, with enthalpy value is 35015.97J.Kinetic rate for temperature 873 K, 973 K and 1073 K is ð‘˜ = 1,484ð‘’ âˆ’2759/ð‘‡ , kinetic rate for temperature 673 K and 773 K is ð‘˜ = 16,5306ð‘’ âˆ’5368/ð‘‡ and ð‘˜ = 3,0373ð‘’ âˆ’2980/ð‘‡ respectively. As the temperature increase, activation energy (Ea) to decompose biomass into gases is decrease.